NMDAR PAMs: Multiple Chemotypes for Multiple Binding Sites - Goldsmith, Paul J (Current topics in medicinal chemistry, 2019)
The N-methyl-D-aspartate receptor (NMDAR) is a member of the ionotropic glutamate receptor (iGluR) family that plays a crucial role in brain signalling and development. NMDARs are nonselective cation channels that are involved with the propagation of excitatory neurotransmission signals with important effects on synaptic plasticity. NMDARs are functionally and structurally complex receptors, they exist as a family of subtypes each with its own unique pharmacological properties. Their implication in a variety of neurological and psychiatric conditions means they have been a focus of research for many decades. Disruption of NMDAR-related signalling is known to adversely affect higherorder cognitive functions (e.g. learning and memory) and the search for molecules that can recover (or even enhance) receptor output is a current strategy for CNS drug discovery. A number of positive allosteric modulators (PAMs) that specifically attempt to overcome NMDAR hypofunction have been discovered. They include various chemotypes that have been found to bind to several different binding sites within the receptor. The heterogeneity of chemotype, binding site and NMDAR subtype provide a broad landscape of ongoing opportunities to uncover new features of NMDAR pharmacology. Research on NMDARs continues to provide novel mechanistic insights into receptor activation and this review will provide a high-level overview of the research area and discuss the various chemical classes of PAMs discovered so far.